Schlaganfallpatienten nach stationärer neurologischer Rehabilitation: Eine prospektive Studie zur Ermittlung von Prädiktoren für das Überleben zuhause bis 5 Jahre nach Entlassung - Grässel, Elmar; Schupp, Wilfried; Schmidt, Ralf (Rehabilitation (Germany), 2019)
Purpose To identify factors influencing the long-term survival at home in stroke patients after neurological inpatient rehabilitation. Methods The study was conducted as a prospective cohort study in 204 stroke patients who were treated in the course of one year in the Herzogenaurach Rehabilitation Hospital (rehabilitation phases C and B). The social data and clinical data were collected during inpatient rehabilitation. The outcome variable was assessed up to 5 years after discharge. Differences between groups were analysed with t-tests or chi-square tests. Binary logistic regression analyses were carried out for multivariate predictor analyses. Results The regression analysis resulted in a prediction model consisting of 5 variables for living at home 2.5 years after discharge (vs. institutionalization or death): a greater increase in health-related quality of life during inpatient rehabilitation, better health-relate quality of life at discharge, a greater increase in functional independence during inpatient rehabilitation, a higher body-mass index and fewer comorbidity conditions associated with a mortality risk. 5 years after discharge the prediction model consists of 3 variables: lower age, fewer comorbidity conditions associated with a mortality risk and lower risk for falls at discharge from neurological rehabilitation. Conclusion Up to 2.5 years after discharge the extent of functional improvement and the improvement of health related quality of life, which are both correlated with therapeutic effects, are predictors for survival and living at home. On the other hand, 5 years after discharge biological factors as age and comorbidities are prognostically dominating.
CRIS-Team Scopus Importer:2019-11-01
Keywords: inpatient neurological rehabilitation; longitudinal study; predictors for living at home; stroke